Melatonin Effects on Non-Alcoholic Fatty Liver Disease Are Related to MicroRNA-34a-5p/Sirt1 Axis and Autophagy - Stacchiotti, Alessandra; Grossi, Ilaria; García-Gómez, Raquel; Patel, Gaurangkumar; Salvi, Alessandro; Lavazza, Antonio; De Petro, Giuseppina; Monsalve, Maria; Rezzani, Rita (Cells (Basel, Switzerland), 2019)
Melatonin, an indole produced by pineal and extrapineal tissues, but also taken with a vegetarian diet, has strong anti-oxidant, anti-inflammatory and anti-obesogenic potentials. Non-alcoholic fatty liver disease (NAFLD) is the hepatic side of the metabolic syndrome. NAFLD is a still reversible phase but may evolve into steatohepatitis (NASH), cirrhosis and carcinoma. Currently, an effective therapy for blocking NAFLD staging is lacking. Silent information regulator 1 (SIRT1), a NAD+ dependent histone deacetylase, modulates the energetic metabolism in the liver. Micro-RNA-34a-5p, a direct inhibitor of SIRT1, is an emerging indicator of NAFLD grading. Thus, here we analyzed the effects of oral melatonin against NAFLD and underlying molecular mechanisms, focusing on steatosis, ER stress, mitochondrial shape and autophagy. Male C57BL/6J (WT) and SIRT1 heterozygous (HET) mice were placed either on a high-fat diet (58.4% energy from lard) (HFD) or on a standard maintenance diet (8.4% energy from lipids) for 16 weeks, drinking melatonin (10 mg/kg) or not. Indirect calorimetry, glucose tolerance, steatosis, inflammation, ER stress, mitochondrial changes, autophagy and microRNA-34a-5p expression were estimated. Melatonin improved hepatic metabolism and steatosis, influenced ER stress and mitochondrial shape, and promoted autophagy in WT HFD mice. Conversely, melatonin was ineffective in HET HFD mice, maintaining NASH changes. Indeed, autophagy was inconsistent in HET HFD or starved mice, as indicated by LC3II/LC3I ratio, p62/SQSTM1 and autophagosomes estimation. The beneficial role of melatonin in dietary induced NAFLD/NASH in mice was related to reduced expression of microRNA-34a-5p and sterol regulatory element-binding protein (SREBP1) but only in the presence of full SIRT1 availability.